DELAYED EPITHELIALIZATION AFTER COMPOSITE GRAFT NECROSIS IN FINGERTIP RECONSTRUCTION: A RARE SALVAGE PHENOMENON - Ocly Davira Putri Laisnima; Agus Roy Rusly Hariantana Hamid; I Gusti Putu Hendra Sanjaya; Shita Diwyani Sudarsa; Astrinita Lestari Suyata; Gede Wara Samsarga (Universitas Airlangga, 2026)
Highlights: Delayed epithelialization occurred beneath a clinically necrotic composite graft, enabling unexpected salvage of a fingertip injury without complex secondary reconstruction. Delayed debridement and necrotomy preserved regenerating tissue and resulted in favorable outcomes in an Allen type III injury. Apparently nonviable composite grafts may still function as a temporary scaffold for epithelial regeneration in selected cases. Abstract: Introduction: Composite grafting is a commonly used technique for fingertip reconstruction after distal digital amputations, but graft necrosis remains a major complication that often requires secondary procedures. This report describes a rare salvage phenomenon involving delayed epithelialization beneath a necrotic composite graft. Case Illustration: A 25‑year‑old male sustained an Allen type III crush injury of the right index fingertip with comminuted distal phalanx fracture. Initial management in the emergency department consisted of wound irrigation, debridement, composite grafting of the amputated segment, and pin fixation under local anesthesia, in accordance with the patient’s preference to avoid surgery in the operating room and to preserve fingertip length. Discussion: Despite progressive graft necrosis, the patient declined early debridement. Three months post-injury, delayed debridement and necrotomy were performed under regional anesthesia. Intraoperatively, epithelialization was unexpectedly identified in the deep tissue layers beneath the necrotic graft. The wound was managed with moist dressings and topical gentamicin. One week post-debridement, a 0.5 × 0.5 cm wound demonstrated crusting and epithelialization without infection. At subsequent follow-up, the patient exhibited minimal pain, restored sensibility, normal joint motion, preserved grip strength, and nail regrowth. Conclusion: Delayed epithelialization beneath necrotic composite grafts is rare. Careful delayed debridement may preserve tissue and avoid secondary reconstruction in selected cases.